Oxidative Stress Defense Module in Lung Cancers: Molecular Pathways and Therapeutic Approaches - Eunsun Lee; Jeong Hee Hong (Antioxidants, 2025)
The regulation of oxidative stress is an effective strategy for treating cancers. Therapeutic strategies for modulating an undesirable redox balance against cancers have included the enhancement of oxidative components, reducing the action of antioxidant systems, and the combined application of radiation and redox-modulating drugs. A precise understanding of redox regulation is required to treat different kinds of cancer. This review focuses on the redox regulation and oxidative stress defense systems of lung cancers. Thus, we highlighted several enzymatic antioxidant components, such as superoxide dismutase, catalase, heme oxygenase-1, peroxiredoxin, glutaredoxin, thioredoxin, thioredoxin reductase, glutathione peroxidase, and antioxidant components, including glutathione, nuclear factor erythroid 2–related factor 2, 8-oxo-7,8-dihydro-2′-deoxyguanosine, and mitochondrial citrate carrier SLC25A1, based on PubMed and Scopus-indexed literature. Understanding the oxidative stress defense system in lung cancer would be beneficial for developing and expanding therapeutic strategies, such as drug development, drug design, and advanced delivery platforms.